Perceived online advertising disruption: Examining the role of blockchain technology among Indian firms - Haq, Zia ul; Altaf, Zaid; Manzoor, Mehak (Frontiers in Blockchain, 2025)
IntroductionThe study explores blockchain technology as a disruptive innovation in digital advertising, emphasizing its role in enhancing transparency, minimizing advertising clutter, and improving return on investment among Indian firms.MethodsPrimary data were collected through a structured questionnaire from 220 technology-oriented firms in Jammu and Kashmir. The study employed exploratory factor analysis (EFA) and canonical correlation analysis to examine relationships among incremental innovation, decision aid, technology trust, perceived disruptive value, and technology adoption.ResultsFindings reveal that incremental innovation, decision aid, and technology trust significantly influence perceived disruptive value, which in turn correlates positively with technology adoption. Minimizing advertising clutter and improving control and transparency emerged as key adoption factors.DiscussionThe results highlight blockchain’s potential to reduce inefficiencies and enhance credibility in online advertising. The study contributes to early empirical understanding of blockchain adoption and its disruptive potential in digital marketing.